Liberalisasi Hukum Perkawinan Di Negara-Negara Barat - Wahyuni, Sri (UIN Sunan Kalijaga, 2014)
This article discusses about the liberalization of Marriage law in the western countries which occurs in line the liberalization of religious values in the societies. Marriage law reform had begun when the religious reform took a place, namely from Catholic to Protestant (Lutheran). In the Catholic era, marriage is a religious affair which was regulated by Church, but in the Protestant era, marriage was the affair from God to humanity. Therefore, marriage law had developed as the development of the human culture. In the western countries, religious marriage is not regarded but they have the civil marriage which is legal according to the state law; and in several western countries, marriage law has accommodated the same sex marriage.